2016
DOI: 10.1093/annonc/mdw184
|View full text |Cite
|
Sign up to set email alerts
|

P21-activated kinase 1 (Pak1) signaling influences therapeutic outcome in pancreatic cancer

Abstract: To our knowledge, this is the first study illustrating the mechanistic role of Pak1 in causing gemcitabine resistance via multiple signaling crosstalks, and hence Pak1-specific inhibitors will prove to be a better adjuvant with existing chemotherapy modality for PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…This protein is presented as a regulator of cytoskeletal remodeling, apoptosis and cell motility. It has been recently demonstrated that nephrotoxicity increases matrix remodeling and apoptosis properties [34,35]. We also report Cdk9, Psma3, Icam1, Myc, Hnrpu, Pak1 and Alb as a consensus early signature of nephrotoxicity that induced by Lead acetate.…”
Section: Discussionsupporting
confidence: 56%
“…This protein is presented as a regulator of cytoskeletal remodeling, apoptosis and cell motility. It has been recently demonstrated that nephrotoxicity increases matrix remodeling and apoptosis properties [34,35]. We also report Cdk9, Psma3, Icam1, Myc, Hnrpu, Pak1 and Alb as a consensus early signature of nephrotoxicity that induced by Lead acetate.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, several reports [4,9,11,15] unraveled the role of Pak1 in the activation of pancreatic stellate cells (PSCs), its involvement in transforming normal pancreatic cells to PDAC and its ability to modulate drug resistance in pancreatic cancer. All these findings suggest that Pak1-specific inhibitors will prove to be a better adjuvant with the existing chemotherapy modality for PDAC.…”
Section: Expert Opinionmentioning
confidence: 99%
“…One possible impeding factor which is difficult to achieve is the selectivity within the PAK family, because of sequence homology among the family members. Although some Pak1 selective inhibitors like IPA-3 [9,[16][17][18][19], FRAX-597 [11,20], G-5555 [12], and Novartis compound 3 [13] have been disclosed, the successful in vivo dose optimization for target specificity and stability is yet to be tested on larger group of animals. …”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAK1 also contributes to therapeutic resistance of cancers of the pancreas [4], colon [5] and lung [1], and thus may become an important target in cancer treatment. We have previously reported that PAK1 stimulates growth and metastasis of colorectal cancer (CRC), through activation of multiple signalling molecules including ERK, AKT [6] and β-catenin [7].…”
Section: Introductionmentioning
confidence: 99%